(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Indigenous villages located near urban centers are undergoing an accelerated process of epidemiological transition, with an increase in the incidence of non-communicable chronic diseases (NCCD). Objectives: To determine the prevalence of NCCD in the indigenous population settled in Aracruz (north coast of Espírito Santo State, Brazil), and to compare the current data with those obtained in the same population in 2003-2004. Methods: The study included 1,084 adults (≥20 years old, 111 non-indigenous and 973 indigenous individuals, including 90 Guarani and 883 Tupiniquim ethnicity) from an eligible population of 2,982 residents (36.4% attending) in the villages. All data were collected at the University Hospital (HUCAM) of Ufes, including blood and urine samples (fasting), as well as anthropometric measurements, bioimpedance, blood pressure, electrocardiogram. Data are presented as mean ± standard deviation or numbers and percentages. Proportions were compared by the Chi-square test, with statistical significance set at p<0.05. Results: The mean age was 41.6 ± 14.8 years, with predominance of women (57.6%) and young adults (20-39 years, 49.9%). The prevalence of obesity was 38.6% (higher in women 47.8% vs. 25.7%; p<0.05), arterial hypertension (39.5%, with 38% with controlled blood pressure with medicines), and diabetes mellitus (13.7%, with half being new diagnosis). Compared to the survey from 2003-4, the prevalence of obesity increased 2.5 times, and diabetes 3 times. Conclusion: The prevalence of major NCCD is high in the studied population, indicating the need for prevention and earlier diagnosis interventions.